2015
DOI: 10.5539/ies.v8n3p55
|View full text |Cite
|
Sign up to set email alerts
|

Goals, Strategies, and Achievements in the Internationalization of Higher Education in Japan and Taiwan

Abstract: International knowledge and skills are essential for success in today's highly competitive global marketplace. As one of the key providers of such knowledge and skills, universities have become a key focus of the internationalization strategies of governments throughout the world. While the internationalization of higher education clearly has certain benefits for students, schools, the national economy, and the international community, each country gives a different degree of importance to each of these variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Rather, the participant's reactions more closely align with the sentiments of other researchers (Ho et al, 2015;Wysokinska, 2009;Picciano, 2006;Lukman & Krajnc, 2012;Mundkur & Ellickson, 2012;Coffey et al, 2013), confirming that a US degree, instruction in the English language, and learning how the developed world has approached certain business practices, can significantly improve the knowledge, information, and local practices in many industries. Picciano (2006) study reported that in Africa a strong desire for better technology, more education and more fluency in the English language for their citizens draws enrollments from this continent.…”
Section: International Student Perceptions Of Online Degreessupporting
confidence: 48%
See 2 more Smart Citations
“…Rather, the participant's reactions more closely align with the sentiments of other researchers (Ho et al, 2015;Wysokinska, 2009;Picciano, 2006;Lukman & Krajnc, 2012;Mundkur & Ellickson, 2012;Coffey et al, 2013), confirming that a US degree, instruction in the English language, and learning how the developed world has approached certain business practices, can significantly improve the knowledge, information, and local practices in many industries. Picciano (2006) study reported that in Africa a strong desire for better technology, more education and more fluency in the English language for their citizens draws enrollments from this continent.…”
Section: International Student Perceptions Of Online Degreessupporting
confidence: 48%
“…Berchem (1991) noted that as professionals and global citizens, students will graduate and work in a crosscultural context where they will, "need to have more knowledge not only of the social, cultural and economic realities, but also of the languages of partner countries" (p. 298). This sentiment was echoed by Ho, Lin, and Yang (2015) and Wysokinska (2009); skills acquired during international knowledge exchanges by students are essential for personal (student) and national success in the global marketplace, and crucial for the development of a knowledge society. To help students with educational opportunities, several different kinds of international opportunities are being pursued by U.S. higher education institutions, including offshore programs.…”
Section: Pursuing Online International Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The opposite example is given in the description of EMI settings in several cultures (Hsuan-Fu et al, 2015;Macaro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to Ho, Lin and Yang (2015), the internationalization of higher education can be defined as "a process of integrating an international dimension into the teaching, research, and service functions of an institution of higher education" [22]. Internationalization can be achieved through a variety of strategies, for example, encouraging students to study abroad, recruiting foreign students, increasing joint degree programs, strengthening cooperation with overseas universities, integrating international knowledge into the curriculum, and promoting the publication of articles in international journals.…”
Section: Globalization and Internationalizationmentioning
confidence: 99%